Bir Huzurevindeki Yaşlılara Verilen Eğitimin Ağız ve Diş Sağlığı Üzerine Etkisi - (:unkn) unknown (My University, 2016)
Amaç: Bu çalışma, bir huzurevindeki yaşlılara verilen eğitimin ağız ve diş sağlığı üzerine etkisini incelemek amacıyla yapılmıştır.Hastalar ve Yöntem: Araştırma İstanbul'da Şubat- Mayıs 2013 tarihleri arasında ön-son test, tek gruplu yarı deneysel araştırma tasarımı ile yürütüldü. Araştırmaya 40 yaşlı dahil edildi. Veri toplama aracı olarak, demografik ve ağız diş sağlığı ile ilgi 40 sorudan oluşan anket formu ve Geriatrik Ağız ve Diş Sağlığı Değerlendirme Formu (GASDF) kullanıldı. Yaşlılara 6-8 kişilik gruplar halinde ağız ve diş sağlığı eğitimi verildi. Eğitimden sekiz hafta sonra son testler uygulandı.Bulgular: Yaş ortalaması 76.90±6.49 olan yaşlıların %60'ı erkekti. Yaşlıların %50'sinde diş yoktu, %77.5'i protez kullanıyordu ve %35'inin ağızlarında yara vardı. Yaşlıların GOHAI'den aldıkları puanlar eğitim sonrasında istatistiksel olarak anlamlı yüksek bulundu (Z=2.96; p=0.003). Eğitim sonrası yaşlıların ağız yarasında azalma oldu.Sonuç: Geriatrik Ağız Sağlığı Değerlendirme Formu puanlarının, diş/protez fırçalama sayısının arttığı; ağız yaralarında azalma olduğu görüldü. Bu anlamda ağız ve diş sağlığı eğitiminin etkili olduğu söylenebilir.

Purpose: This study was conducted to determine the effect of education on the mouth and dental health of elderly individuals living in a rest home. Patients and Methods: The study was carried out at a rest home operating under the auspices of the Ministry of Family and Social Policies in Istanbul over the period February-May 2013, using pre-/post-tests and a single-group semi-experimental research design. The subjects for the research were 40 elderly individuals. A questionnaire with 40 questions on demographics and mouth and dental health was used as a data collection instrument, as well as the Geriatric Oral Health Assessment Index (GOHAI). The elderly were divided into groups of 6-8 and given education on mouth and dental health. The post-tests were administered eight weeks after the education was completed. Results: Of the elderly individuals, whose mean age was 76.90±6.49, 60% were men. Fifty percent did not have any teeth, 77.5% had dental prostheses and 35% had sores in their mouths. The scores the individuals received in the GOHAI were found to have increased significantly after the education (Z=2.96; p=0.003). A lesser number of mouth sores were seen in the elderly after the education. All of the individuals who had not been brushing their teeth/prostheses prior to the education started the habit afterwards. Conclusion: The education given to the elderly resulted in an increase in their scores on The Geriatric Oral Health Assessment Index, an increase in brushing their teeth/prostheses, a decrease in a number of mouth sores.
The Effect Of Educatıon On Mouth And Dental Health Of The Elderly At A Rest Home
Keywords: Geriatri ve Gerontoloji